Proses Pembuatan Sabun Cair Berbahan Baku Pepaya (Carica papaya L.) dan Desain Produk menggunakan Aplikasi Canva - Nur Insani Amir; Arafah Nurfadillah; Ade Irma; Juniati Binti Lukman; Muh. Fadli (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Soap is a substance whose majority of its raw materials come from chemicals and use as body cleanser. Soap can be said as an item that must be fulfilled considering its very vital function. Papaya (Carica papaya L.) is a plant that contains secondary metabolites that have important functions for the body such as alkaloids, capin carikaxanthin, papain, saponins, flavonoids and tannis which have pharmacological effects as antibacterial. This activity is descriptive and experimental in nature, starting from the process of delivering material, question and answer sessions, carrying out experimental processes, packing processes and product designs. The purpose o this study is that students can find out the process of making soap made from papaya, which is a home industry-based production process.